The Regulation of Notch Signaling in Retinal Development and Regeneration - Mills, Elizabeth A. (Curr Pathobiol Rep, 2017)
PURPOSE OF REVIEW: Notch signaling is an important component of retinal progenitor cell maintenance and MG specification during development, and its manipulation may be critical for allowing MG to re-enter the cell cycle and regenerate neurons in adults. In mammals, MG respond to retinal injury by undergoing a gliotic response rather than a regenerative one. Understanding the complexities of Notch signaling may allow for strategies that enhance regeneration over gliosis. RECENT FINDINGS: Notch signaling is regulated at multiple levels, and is interdependent with various other signaling pathways in both the receptor and ligand expressing cells. The precise spatial and temporal patterning of Notch components is necessary for proper retinal development. Regenerative species undergo a dynamic regulation of Notch signaling in MG upon injury, whereas non-regenerative species fail to productively regulate Notch. SUMMARY: Notch signaling is malleable, such that the altered composition of growth and transcription factors in the developing and mature retinas result in different Notch mediated responses. Successful regeneration will require the manipulation of the retinal environment to foster a dynamic rather than static regulation of Notch signaling in concert with other reprogramming and differentiation factors.